2017
DOI: 10.1016/j.jaci.2016.08.048
|View full text |Cite
|
Sign up to set email alerts
|

U-BIOPRED clinical adult asthma clusters linked to a subset of sputum omics

Abstract: Clustering based on clinicophysiologic parameters yielded 4 stable and reproducible clusters that associate with different pathobiological pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

9
206
3
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 252 publications
(222 citation statements)
references
References 37 publications
9
206
3
4
Order By: Relevance
“…Although the authors have already reported clinical and pathological clustering analyses [15], and found four phenotypes not much different from those previously reported [20,21], they reasoned that clustering severe asthma using clinical features may not only not provide a precise definition of severe asthma, but may even preclude the collection of adequate information on the underlying mechanisms of each phenotype. Indeed, significant overlap of inflammatory profiles and inflammatory mechanisms is present across clinical clusters.…”
mentioning
confidence: 80%
See 4 more Smart Citations
“…Although the authors have already reported clinical and pathological clustering analyses [15], and found four phenotypes not much different from those previously reported [20,21], they reasoned that clustering severe asthma using clinical features may not only not provide a precise definition of severe asthma, but may even preclude the collection of adequate information on the underlying mechanisms of each phenotype. Indeed, significant overlap of inflammatory profiles and inflammatory mechanisms is present across clinical clusters.…”
mentioning
confidence: 80%
“…It would be important to revisit the clinical phenotype recently identified from the U-BIOPRED cohort [15] and assess the consistency/concordance with the transcriptomic clusters reported here and evaluate their clinical relevance. A possible validation would be to show differences in outcomes among the three TAC groups in a validation set.…”
mentioning
confidence: 89%
See 3 more Smart Citations